The disempowerment of the judiciary in Syria since the March revolution of 2011 and the emergence of off-bench resistance to authoritarian rule: What role for women judges and prosecutors? - Monique Cardinal (Oñati Socio-Legal Series)
The Arab uprisings of 2010-2011 generated a growing movement for change among the judicial corps throughout the Arab world. Judges and prosecutors created independent associations in Morocco, Mauritania, Yemen, Libya, Lebanon, and Tunisia to represent their interests and promote a better administration of justice. Since the March Revolution of 2011 in Syria, members of the judiciary also attempted to create their own association, but failed to do so. This article briefly outlines the demographics of the judicial corps after ten years of conflict in Syria. A noticeable change is the increase in the number of women in the judiciary and their promotion to positions of power. How have women judges and prosecutors used the greater authority granted to them? To the advantage of the regime, as a means for self-promotion or to better defend the rights of all? The second part of the article details the progressive disempowerment of the judiciary, the expansion of the criminal justice system and the creation of the Counterterrorism Court used by the regime to quash the popular uprising. In the final section, stories of off-bench resistance highlight efforts made by judges and prosecutors to defend their judicial autonomy and the basic human rights and freedoms of all Syrians.